2019
DOI: 10.3889/oamjms.2019.608
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Manifestation of Coronary Artery Disease and Determining the Role of Effective Factors in the Need for Pacemaker Insertion in These Patients

Abstract: BACKGROUND: Many patients who are candidates for a pacemaker are also at the same time risk factors for coronary artery disease such as high blood pressure, hypertension, diabetes, and hyperlipidemia, and therefore the probability of having coronary artery disease is significant. Effective diagnostic measures can be taken to prove the factors affecting the incidence of CAD in patients undergoing pacemakers at high-risk, including angiography. Therefore, it can prevent complications during and after pacemaker i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…These proportions represent the complexities of CAD presentations in the setting of bradyarrhythmias requiring pacemaker implantation. Previous studies have observed incidences of obstructive CAD within the ranges of 13.7%–34.4% based on different definitions, 10 , 12 , 13 which are higher than the findings of our current study (12.45%). This highlights the diverse nature of our patient group and underscores the importance of studying the interaction between bradyarrhythmias and CAD.…”
Section: Discussioncontrasting
confidence: 93%
“…These proportions represent the complexities of CAD presentations in the setting of bradyarrhythmias requiring pacemaker implantation. Previous studies have observed incidences of obstructive CAD within the ranges of 13.7%–34.4% based on different definitions, 10 , 12 , 13 which are higher than the findings of our current study (12.45%). This highlights the diverse nature of our patient group and underscores the importance of studying the interaction between bradyarrhythmias and CAD.…”
Section: Discussioncontrasting
confidence: 93%